Developing Critical Thinking of Students on Elementary Education Level - Pisoňova, Mária (Wydawnictwo Naukowe UAM, 2014)
Critical thinking should be purposefully developed in the primary stage of education as the evaluation is a very important ability which enables us to make decisions effectively in the newly emerged life situations. The ability to decide is conditioned by critical thinking which facilitates adequate reactions in specific situations and in concord with oneself.
Rozwój krytycznego myślenia u studentów studiów nauczycielskich w zakresie edukacji elementarnej
Keywords: axiology of personality; critical thinking; values; creative – humanistic education